Analisis Perancangan dan Pengujian Alat Cuci Tangan Otomasis Berbasis Energi Surya 100 WP - Heri Suripto; Unggul Satria Jati (Politeknik Negeri Cilacap, 2021)
The outbreak of the Covid 19 disease has caused disaster to the people. The emergence of this disease’s outbreak encourages the importance clean lifestyle. In order not to easily contracted the Covid 19 disease, it is necessary to make automatic handwashing equipment to prevent people from having direct contact with the equipment. In this research the design and testing of an automatic handwashing equipment based on solar energy were carried out. The purpose of this research was to determine the capacity of the sun's intensity to provide electrical energy through the solar module to the battery which will be used to supply electrical energy of solar energy-based automatic handwashing equipment. The method used in this research was the Palh and Beitz method approach and the experimental method which started with the design, material selection, assembly and testing. The design produced equipment specifications for a solar module framework with a height of 100 cm, a width of 80 cm, a length of 100 cm, while for a sink frame with a height of 90 cm, a width of 45 cm, and a length of 55 cm. The test was carried out in three phases, phase one was testing the module input power. The module input power in the test produced a power of 2461 Watts with a solar radiation intensity of 3237 W / m2. The peak intensity and power of the sun was shown at 13.00 WIB. The second phase of the test was the length of time needed to charge the battery took 2.5 hours. The third phase of the test was the power needed for sensors and pumps of 358 Watts. The power requirement of 358 Watts could be supplied by a 100 Wp solar panel, since the power released from a 100 Wp solar panel is 400 Watts.